Gingival pigmentation in relation to anti-inflammatory salivary interleukin 10, a comparative study - Ahmed Shukur Mahmood,; Ban Sahib Diab, (Journal of the Pakistan Medical Association, 2024)
Objective: To assess gingival pigmentation prevalence among students, and its relationship with anti-inflammatory salivary interleukin-10. Method: The observational, cross-sectional, comparative study was conducted at the College of Physical Education and Sport Sciences, Diyala University, Iraq, from December 2021 to March 2022, and comprised students of either gender aged 19-22 years. Students with pigmented gingiva were in group A, while those having no gingival pigmentation were in group B. The level of interleukin-10 was tested using enzyme-linked immunosorbent assay in both groups, and values were compared using the gingival pigmentation index. Data was analysed using SPSS 22. Result: Of the 1,295 students assessed, 1,044(80.62%) were males and 251(19.38%) were females. Pigmented gingiva was found in 118(9.11%), and these students represented group A, while as many subjects were enrolled in controlled group B. Pigmented gingiva was more common among males 81(68.64%) than females 37(31.36%). Salivary interleukin-10 level was significantly increased in group A compared to group B (p<0.05). However, there were no significant differences in mean value of salivary interlukin-10 with respect to severity in group A (p>0.05). Conclusion: Pigmentation was beneficial in terms of gingival protection. Key Words: Gingiva, Interleukin, Pigmentation, Enzyme, Immunosorbent,